(untitled) (Scientific Journal for Publishing in Health Research and Technology, 2026)
The method for giving birth to babies in the Tarhuna area of Libya is now through Caesarean section (C/S), which is on the rise. There have been several factors not related to a mother’s medical issue that have contributed to the high C/S rate including: the mother’s desire for a C/S; the war in Libya leading to a lack of stability in the country; the financial incentive for providers to do C/S’s; the lifestyles of the many women; and the quality of the healthcare profession in Libya. The aim of this study is to assess the rate of C/S’s performed at both public and private hospitals as well as to investigate what factors have influenced the increase in C/S’s at both public and private hospitals. The study included data collected from 1607 births delivered at a public and private hospital in Tarhuna over a period of seven months (January, February, March, April, May, June, and July 2020) to evaluate the number of C/S’s performed as compared to the number of normal vaginal deliveries. The findings of the study were as follows: The rate of C/S’s at the public hospital located in Tarhuna was 55.27% of all births performed; whereas at the private hospital located in Tarhuna, 59.79% of all births performed were C/S’s. Based on the findings of this research, it has been concluded that C/S’s in Tarhuna exceed WHO recommendations and exceed C/S rates for some neighboring Arab countries.